Testing the Waters: Behavior across Participant Pools - Erik Snowberg; Leeat Yariv (Center for Economic Studies and ifo Institute (CESifo), 2018)
We leverage a large-scale incentivized survey eliciting behaviors from (almost) an entire university student population, a representative sample of the U.S. population, and Amazon Mechanical Turk (MTurk) to address concerns about the external validity of experiments with student participants. Behavior in the student population offers bounds on behaviors in other populations, and correlations between behaviors are largely similar across samples. Furthermore, non-student samples exhibit higher measurement error. Adding historical lab participation data, we find a small set of attributes over which lab participants differ from non-lab participants. Using an additional set of lab experiments, we see no evidence of observer effects.
Keywords: B41; C80; C90; 330; lab selection; external validity; experiments